Low or oscillatory shear stress and endothelial permeability in atherosclerosis - Chen, Li; Qu, Hua; Liu, Bin; Chen, Bing-Chang; Yang, Zhen; Shi, Da-Zhuo; Zhang, Ying (Frontiers in Physiology, 2024)
Endothelial shear stress is a tangential stress derived from the friction of the flowing blood on the endothelial surface of the arterial wall and is expressed in units of force/unit area (dyne/cm 2 ). Branches and bends of arteries are exposed to complex blood flow patterns that generate low or oscillatory endothelial shear stress, which impairs glycocalyx integrity, cytoskeleton arrangement and endothelial junctions (adherens junctions, tight junctions, gap junctions), thus increasing endothelial permeability. The lipoproteins and inflammatory cells penetrating intima due to the increased endothelial permeability characterizes the pathological changes in early stage of atherosclerosis. Endothelial cells are critical sensors of shear stress, however, the mechanisms by which the complex shear stress regulate endothelial permeability in atherosclerosis remain unclear. In this review, we focus on the molecular mechanisms of the endothelial permeability induced by low or oscillatory shear stress, which will shed a novel sight in early stage of atherosclerosis.